Formulasi dan Uji Penyembuhan Luka Sayat Sediaan Krim Ekstrak Metanol Daun Kelor (Moringa oleifera Lam.) pada Kelinci (Oryctolagus cuniculus) - Kristyanti, Yulia; More, Evanisia (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
The development of a cut wound cream dosage form from Moringa (Moringa oleifera Lam.) leaf extract has been carried out. The purpose of this study was to determine the most optimal dose of moringa leaf extract cream preparation that can heal cut wounds in male rabbits (Oryctolagus cuniculuc). Moringa leaves were macerated with 96% methanol, cream formulation with varying doses of extract, namely 10% (F I), 12% (F II), 14% (F III), negative control (cream base without extract) and positive control (Bionect). Healing test on male rabbit skin that has been given skin incision treatment for all formulas and controls. The results showed that the test animals gave a healing effect on the average decrease in wound length successively in each treatment group, namely positive control, F III, F II, FI and negative control showed an average decrease in wound length of 0.75 cm, 0.76 cm, 0.87 cm, 1.02 cm and 1.19 cm on the11, 12, 13 and 14 days.